An Inflammation-Centric View of Neurological Disease: Beyond the Neuron - Skaper, Stephen D.; Facci, Laura; Zusso, Morena; Giusti, Pietro (Frontiers in Cellular Neuroscience, 2018)
Inflammation is a complex biological response fundamental to how the body deals with injury and infection to eliminate the initial cause of cell injury and effect repair. Unlike a normally beneficial acute inflammatory response, chronic inflammation can lead to tissue damage and ultimately its destruction, and often results from an inappropriate immune response. Inflammation in the nervous system ('neuroinflammation'), especially when prolonged, can be particularly injurious. While inflammation per se may not cause disease, it contributes importantly to disease pathogenesis across both the peripheral (neuropathic pain, fibromyalgia) and central (e.g. Alzheimer disease, Parkinson disease, multiple sclerosis, motor neuron disease. ischemia and traumatic brain injury, depression, and autism spectrum disorder) nervous systems. The existence of extensive lines of communication between the nervous system and immune system represents a fundamental principle underlying neuroinflammation. Immune cell-derived inflammatory molecules are critical for regulation of host responses to inflammation. Although these mediators can originate from various non-neuronal cells, important sources in the above neuropathologies appear to be microglia and mast cells, together with astrocytes and possibly also oligodendrocytes. Understanding neuroinflammation also requires an appreciation that non-neuronal cell – cell interactions, between both glia and mast cells and glia themselves, are an integral part of the inflammation process. Within this context the mast cell occupies a key niche in orchestrating the inflammatory process, from initiation to prolongation. This review will describe the current state of knowledge concerning the biology of neuroinflammation, emphasizing mast cell-glia and glia-glia interactions, then conclude with a consideration of how a cell’s endogenous mechanisms might be leveraged to provide a therapeutic strategy to target neuroinflammation.